Blood Pressure and Its Association with Gender, Body Mass Index, Smoking, and Family History among University Students - Hussein H. Alhawari; Sameeha Al-Shelleh; Hussam H. Alhawari; Aseel Al-Saudi; Dina Aljbour Al-Majali; Leen Al-Faris; Saif Aldeen AlRyalat (International Journal of Hypertension, 2018)
Hypertension is one of the major risk factors associated with cardiovascular diseases. In this study, we will assess the frequency of hypertension among healthy university students and its association with gender, body mass index, smoking, and family history of both hypertension and cardiovascular diseases. We screened healthy university students ranging from 18 to 26 years of age. For each participant, we performed blood pressure measurements using a previously validated device and obtained demographic data, body mass index (BMI), smoking status, and family history of both hypertension and cardiovascular diseases. Out of the total number of 505 participants included in this study, 35.2% have blood pressure between 130/80 and 139/89, and 13.5% have blood pressure of more than 140/90. We found significant gender differences in both systolic pressure (p = 0.003) with mean difference = 18.08 mmHg (CI: 16.13 to 19.9) and diastolic pressure (p = 0.011) with mean difference = 3.6 mmHg (CI: 2.06 to 5.14), higher in males than in females. Upon comparing the mean difference in both systolic and diastolic blood pressure with BMI, we found significant differences in both systolic (p < 0.001) and diastolic (p = 0.002) blood pressure. We also found that smokers have significantly (p = 0.025) higher systolic blood pressure (mean difference = 4.2 mmHg, CI: 3.2 mmHg to 8.8 mmHg), but no significant difference for diastolic blood pressure (p = 0.386), compared to nonsmokers. First-degree family history of both hypertension and cardiovascular diseases affected systolic but not diastolic blood pressure. Taking into account the adverse short- and long-term effect of hypertension, we recommend adopting an awareness program highlighting the importance of screening blood pressure in young adolescent populations, keeping in mind that both high BMI and smoking are important modifiable factors.